2016
DOI: 10.1371/journal.pone.0146918
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of the Prevalence and Correlates of Self-Harm in Juvenile Detention

Abstract: BackgroundSuicide is the number one cause of death among incarcerated youth. We examined the demographic and forensic risk factors for self-harm in youth in juvenile detention using a Canadian provincial correctional database.MethodWe analyzed data from de-identified youth aged 12 to 18 at the time of their offense who were in custody in a Manitoba youth correctional facility between January 1, 2005 and December 30, 2010 (N = 5,102). Univariate and multivariate logistic regression analyses determined the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
5
1
10
Order By: Relevance
“…[51][52][53][54][55][56] In detained adolescents, the prevalence of suicidal ideation ranged from 12•7% to 59•0% over the lifetime, 57 40,41,59,65 For both sexes combined, the prevalence of suicide attempts was 1•9-6•6% during the past month and 13•3-35•0% during the past year (appendix p 10). 11,28,29,41,45,[57][58][59][60][61][62][63][64]66,67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The prevalence 57,59,78 Although suicide accounted for ≤1% of all deaths among adolescents in detention, 11,74,83 the risk of suicide following release from detention is estimated to be two to nine times greater than that of their agematched and sexmatched peers. 6,11,…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53][54][55][56] In detained adolescents, the prevalence of suicidal ideation ranged from 12•7% to 59•0% over the lifetime, 57 40,41,59,65 For both sexes combined, the prevalence of suicide attempts was 1•9-6•6% during the past month and 13•3-35•0% during the past year (appendix p 10). 11,28,29,41,45,[57][58][59][60][61][62][63][64]66,67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The prevalence 57,59,78 Although suicide accounted for ≤1% of all deaths among adolescents in detention, 11,74,83 the risk of suicide following release from detention is estimated to be two to nine times greater than that of their agematched and sexmatched peers. 6,11,…”
Section: Resultsmentioning
confidence: 99%
“…A Alemanha três estudos 10,34,38 independentes e outros dois em conjunto com a Suíça 33,73 . O Canadá 48,57,65,75 realizou quatro estudos, Cingapura 37,77,79 , Israel 35,45,70 , Itália 12,18,41 O número de artigos encontrados nesta revisão demonstra o interesse da comunidade científica e a relevância do tema, visto a quantidade de publicações e a diversidade de países envolvidos. A América Latina não apresentou produções científicas nos últimos cinco anos ou realizou publicações em revistas sem indexação nas grandes bases.…”
Section: Caracterização Da Amostraunclassified
“…Outros sete trabalhos recrutaram as amostras em locais diversos 9,20,35,37,40,65,68 . De um modo geral, a concentração de estudos em escolas era esperada, uma 34,[36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]62,63,[65][66][67][68][69]72,73,[74][75][76][77][78][79] , havendo oito que incluíram apenas adolescentes do sexo feminino 9,10,33,35,…”
Section: Caracterização Da Amostraunclassified
“…In fact, the leading cause of death in youth custodial settings is suicide [ 17 ]. Justice-involved youth have often endured cumulative adverse life experiences and present with behavioural and emotional problems [ 4 , 16 , 18 20 ]. Many of these environmental and clinical concerns are consistent with the risk factors for self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of the literature on self-harm and suicide is focused on adults and young people who have not been exposed to the justice system. Research has identified the prevalence and correlates of both in custody and lifetime self-harm among youth justice populations [ 16 , 18 23 ]. However, there have been few studies of the prevalence of self-harm in young people in detention in Australia.…”
Section: Introductionmentioning
confidence: 99%